2005
DOI: 10.1191/0267659105pf797oa
|View full text |Cite
|
Sign up to set email alerts
|

Performance of polymethyl pentene oxygenators for neonatal extracorporeal membrane oxygenation: a comparison with silicone membrane oxygenators

Abstract: Small PMP oxygenators (Medos Hilite 800 LT) provide adequate gas exchange and offer technical advantages in terms of more efficient priming, reduced haemodynamic resistance and better control and preservation of coagulation proteins than silicone oxygenators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…It has been reported that hollow fiber membrane oxygenators have lower resistance to blood flow and induce significantly lower pressure drops compared with flat-sheet membrane and silicone membrane oxygenators, and thus, they are more suitable for pulsatile flow. 12,19,31 In addition, the structure and designs of hollow fiber membrane oxygenators have been found to have various impacts on pressure drops and quality of pulsatility as determined by EEP and SHE. 32 Also, a large part of hemodynamic energy has been reported to be absorbed by the arterial filter and arterial tubing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hollow fiber membrane oxygenators have lower resistance to blood flow and induce significantly lower pressure drops compared with flat-sheet membrane and silicone membrane oxygenators, and thus, they are more suitable for pulsatile flow. 12,19,31 In addition, the structure and designs of hollow fiber membrane oxygenators have been found to have various impacts on pressure drops and quality of pulsatility as determined by EEP and SHE. 32 Also, a large part of hemodynamic energy has been reported to be absorbed by the arterial filter and arterial tubing.…”
Section: Discussionmentioning
confidence: 99%
“…While the Medtronics 0800 (Medtronic Inc.) provides some benefits, like 100% gas exchange and high maximum flow rate (1.5 L/ min), its negative aspects, such as a higher preoxygenator pressure and pressure drop, higher resistance to blood flow, and depletion of pulsatility, impede ECLS circuit improvement. Hollow-fiber membrane oxygenators have adequate gas exchange, lower priming volumes, better preservation of coagulation proteins, low plasma leakage, and better hemodynamic characteristics (11,17). With pulsatile perfusion, this…”
Section: Discussionmentioning
confidence: 99%
“…Six MHF patches were affixed with polycin/vorite glue (60% Polycin, 40% Vorite by mass, Cas Chem) in a 50 mL conical tube. PMP MHFs were chosen due to an asymmetric geometry, which is attractive for its resistance to plasma weeping and would theoretically not experience increased plasma weeping if made hydrophilic by surface modification to support cell adhesion (Khoshbin et al, 2005;Lawson and Holt, 2007;Toomasian et al, 2005). Select groups of fiber patches were exposed to radio frequency glow discharge (RFGD; March Plasma Systems, Concord, CA) treatment while in the conical tube (0.3 Torr vacuum and ammonia gas for 60 s at 100 W).…”
Section: Surface Modification Of Mhfs To Support Endothelial Cell Growthmentioning
confidence: 99%